MECHANISTIC ANALYSIS OF THE 3-METHYLLUMIFLAVIN-PROMOTED OXIDATIVE DEAMINATION OF BENZYLAMINE - A POTENTIAL MODEL FOR MONOAMINE-OXIDASE CATALYSIS - KIM, JM; BOGDAN, MA; MARIANO, PS (AMER CHEMICAL SOC, 1993)
An investigation designed to probe flavin-promoted oxidative deaminations of amines is described. 3-Methyllumiflavin (3MLF) has been found to promote clean conversion of benzylamine to N-benzylbenzaldimine under acid (HCl or MgCl2) catalyzed, thermal (80-degrees-C) conditions. The reaction is subject to multiple turnover. Amine structure (1-degrees > 2-degrees > 3-degrees) and alpha-electrofugal group leaving ability (TMS+ > H+) are found to influence reactivity. In addition, the internal d-isotope effect measured for the ground-state reaction by using PhCHDNH2 is found to be 4.3, a value greatly different from the 1.6 measured for the excited-state (SET) reaction run under nearly identical (20-degrees-C rather than 80-degrees-C) conditions. Additional mechanistic information has come from observations which show that benzylamine undergoes instantaneous reaction with N5-ethyl-3-methyllumiflavinium perchlorate to produce a stable 4a-adduct. In addition, this adduct is transformed quantitatively to N-benzylbenzaldimine when treated with benzylamine at 60-degrees-C. These results suggest that the ground-state reaction of PhCH2NH2 promoted by 3MLF follows a polar mechanism involving formation of and elimination in a covalent 4a-(N-benzylamino)dihydroflavin intermediate.
Keywords: ELECTRON-TRANSFER PHOTOCHEMISTRY; CATION RADICALS; AMINE OXIDASE; FLAVIN; PHOTOADDITIONS; INHIBITION; GENERATION; PATHWAYS; SYSTEM